Statistical analysis of seawater ballast tank corrosion data - Md. Noor, Norhazilan (2006)
High variability of corrosion wastage has been acknowledged as a factor that contributes to the uncertainties in corrosion assessment. Hence, statistical analysis on a collection of corrosion measurements seems to be one of the best options to express corrosion rates appropriately. This paper demonstrates an alternative approach to analysing corrosion data randomly collected from seawater ballast tank structure. A statistical time-dependent corrosion depth model is proposed in this paper to improve corrosion interpretation. The new statistical model can be used to predict the likely variation of corrosion depth at any point of time/ age of the vessel. The proposed model intends to simplify the modelling process so the available data can be fully utilised for prediction purposes.